INITIATING A SHARIA AUDIT MODEL FOR ZAKAT MANAGEMENT ORGANIZATIONS IN INDONESIA - Riani, Deni (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2022)
The proliferation of zakat management organizations in Indonesia is part of the zakat problem in Indonesia. The zakat management organization as an intermediary organization between muzaki and mustahiq must have a management basis that is trustworthy, professional, transparent and accountable. The presence of Law Number 23 of 2011 and Government Regulation Number 14 of 2014 provides a legal basis for sharia audits to be carried out as a guarantee of security and comfort for muzakki in paying zakat through BAZNAS and LAZ. The main objective of the shariah audit is to provide certainty of compliance with sharia rules both in terms of collection, distribution and utilization of zakat. This study describes the basic concepts in carrying out sharia audits of zakat management organizations, where there are several main things that must be carried out in carrying out sharia audits of zakat management organizations based on existing laws and general provisions in conducting audits in general as part of the guidelines that must be adhered to. . With the sharia audit carried out, it will increase public confidence in paying zakat through zakat institutions. The sharia audit framework for zakat management organizations includes the planning, implementation and reporting stages and the last is in the form of an opinion on the audit implementation in the form of a statement that is appropriate or not appropriate and then recommendations for improvement on the implementation of the audit.